Regulation of HTLV-1 transcription and deregulated gene expression by the virally-encoded protein Tax - Livengood, Jill A., author; Nyborg, Jennifer, advisor; Laybourn, Paul, committee member; Luger, Karolin, committee member; Fox, Michael D., committee member; LaRue, Susan M., committee member (Colorado State University. Libraries, 2004)
Human T-cell Leukemia Virus Type-1 (HTLV-1) is the etiological agent of Adult T-cell Leukemia/Lymphoma (ATLL) and Tropical Spastic Paraparesis/HTLV-1 Associated Myelopathy (TSP/HAM). Oncogenesis associated with HTLV-1 is linked to the virally encoded transcription factor Tax. In combination with other cellular transcription factors, Tax activates transcription by interacting with the cellular transcription factor CREB, and the cellular coactivator CBP/p300. In addition to activating transcription, Tax has also been shown to disrupt many cellular processes that may lead to malignant transformation. We have identified a possible mechanism for the ability of Tax to deregulate cellular function. The tumor suppressor p53 is mutated in over 60% of all cancers; however, the majority of tumor cells transformed by HTLV-1 display wild-type p53. To regulate transcription, p53 and Tax both utilize the cellular coactivator CBP/p300. We identified a domain on CBP/p300 responsible for binding p53. Tax and p53 compete for binding to this domain, possibly sequestering CBP/p300 in the cell, and limiting p53 access to these critical coactivators. The most studied function of Tax is to activate viral transcription. However, HTLV-1 transcription is a complex process that requires many cellular transcription factors including Sp1. Sp1 has previously been shown to bind at two distinct locations on the HTLV-1 promoter. We demonstrate that Sp1 binds with the highest affinity to the Sp1 site located between the second and third viral CREs. Sp1 is detected at the chromosomally integrated HTLV-1 promoter in living cells in both the absence and presence of Tax. Sp1 activates transcription modestly in vitro and in vivo in the absence of Tax, and a double point mutation at the preferred Sp1 binding site strongly down-regulates basal level transcription. These studies suggest a role for Sp1 in basal, and Tax-independent transcription of HTLV-1. Understanding the transcriptional activation of HTLV-1 is important for developing treatments for individuals who are infected with the virus. There are no current treatments for HTLV-1, and the median survival rate for a person diagnosed with ATL is roughly six months. Polyamides are DNA binding drugs designed to disrupt transcription factor binding and inhibit gene expression. We designed and synthesized six Tax-directed pyrole-imidazole polyamides specifically designed to block Tax binding to DNA at the HTLV-1 promoter. We found that four of these polyamides disrupt binding of the Tax/CREB complex in vitro, and that these same molecules also inhibit Tax-mediated transcription in vitro. However, of these four Tax/CREB-specific polyamides, only one polyamide appears to be uniquely Tax specific. We show that polyamides can enter the nuclei of HTLV-1 infected T-cells, and two of the four polyamides down-regulate virion production in these cells. In addition to down-regulating the functions of p53, Tax has also been shown to deregulate cellular transcription through its effect on the functions of the cellular NF-kB family of proteins. The majority of the studies in the past have focused on the ability of Tax to target regulatory NF-kB proteins in the cytoplasm, which leads to an increase in the levels of NF-kB in the nucleus. However, colocalization studies have shown that Tax and NF-kB reside together in transcriptionally active nuclear bodies. We have studied the mechanisms of Tax deregulation via the NF-kB proteins by focusing on the events that occur directly at the promoters of NF-kB-responsive genes in an in vitro transcription system. We found no direct ability of Tax to deregulate the function of NF-kB at the NF-kB responsive promoter.
Keywords: molecular biology; microbiology; biochemistry